Local Economic Development (PEL) Strategy Based on Coffee Farming Using a Hexagonal Approach in the Ermera District of the República Democrática De Timor-Leste (RDTL) - Caetano Correia; Cristino Gusmao (Universitas 17 Agustus 1945 Surabaya, 2024)
Local economic development as one of the regional development strategies in RDTL needs to be considered as an alternative policy. The led scheme requires active cooperation between the government sector - private sector - NGO - community. Timor coffee is one of the leading products of Timor Leste at this time. The development of LEd based on coffee agricultural products can be used as an alternative to poverty alleviation in Timor Leste. The development of Timor Coffee based on LED requires a strong commitment from all stakeholders, especially in building the nation and local branding.